Factors causing sharia banking students have not transformed from conventional bank to sharia bank (case study of sharia banking students 2018 UIN Syahada Padangsidimpuan) - Latifa Ayunda Sari Panggabean; Nofinawati; Ananda Anugrah Nasution (Prodi Manajemen Zakat dan Wakaf, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Langsa, 2023)
Abstract Purpose – This study aims to identify and describe the factors behind Islamic Banking students Batch 2018 not using Islamic banks in their transaction activities in daily life. Method -This type of research uses field research (Field Research) which is descriptive qualitative in nature. The study uses two data sources, namely primary data and secondary data, as well as data collection techniques through observation, interviews and documentation. Then according to the data analyzed inductively. Research Results - Based on the results of the study, it can be concluded that the causative factor for Islamic Banking students class of 2018 has not transformed from conventional banks to Islamic banks, namely because people generally carry out transactions at conventional banks because they know more about the existence of conventional banks than Islamic banks and the existence of conventional branches that are close to them. with homes, family and closest relatives still using conventional banks in conducting transactions and not feeling the need for a sharia bank yet, the location of Islamic banks is still very minimal, ATM facilities and branches are still few, and there is trauma to their own experiences or those closest to them due to lack of service from Islamic banks. Limitations – This study has limitations in terms of the relatively small number of research subjects. Practical Implications - As a practical implication, the results of this study can be used as a reference by Islamic banking as a strategy to increase the number of users.